CONCEPTS OF WORTHY WORK OF CIVIL SERVANTS IN THE LAW ENFORCEMENT FIELD OF UKRAINE - Panchenko, M. (Київський національний університет імені Тараса Шевченка, 2019)
The article focuses on the comprehensive establishment of the essence of the “decent work of a public servant in the law enforcement sphere” concept. To achieve the stated research goal, the author first clarifies the nature and general significance of the “dignity” phenomenon, and the useful potential for ensuring the dignity of a civil servant in official labor relations. Considering this and the general approaches of scientists to understanding the structure of the decent work signs (criteria), the conceptual content of decent work in the public service in the law enforcement sphere of Ukraine is established and the main criteria for decent work of public servants in the relevant field are determined.

Стаття присвячена комплексному встановленню сутності поняття «гідна праця державного службовця у сфері правоохорони». Для досягнення поставленої дослідницької мети автор спершу уточнює сутність та загальну значимість феномену «гідність», а також корисний потенціал забезпечення гідності держслужбовця у службово-трудових правовідносинах. Зважаючи на це та на загальні підходи вчених до розуміння структури ознак (критеріїв) гідної праці, встановлюється концептуальний зміст гідної праці на державній службі у правоохоронній сфері України та визначаються основні критерії гідної праці держслужбовців у відповідній сфері.
ПОНЯТТЯ ГІДНОЇ ПРАЦІ ДЕРЖАВНИХ СЛУЖБОВЦІВ У ПРАВООХОРОННІЙ СФЕРІ УКРАЇНИ
Keywords: realization of the right; decent work; state service; criteria for decent work; law enforcement sphere; гідна праця; гідність; державний службовець; критерії гідної праці; правоохоронна сфера.